Training Manual on Climate-Smart Agriculture (CSA) Investment Planning for Zambia - Jalango, Dorcas Anyango (2025)
The training manual was developed under the AICCRA project through a collaborative effort between the Ministry of Agriculture (Zambia) and the Alliance of Bioversity International and CIAT to complement the Ministry’s efforts to facilitate trainings on Climate-Smart Agriculture (CSA). It simplifies and operationalizes Zambia’s CSA Investment Plan and complements the ZAMGRO CSA Training Manual. Its purpose is to unpack CSAIP findings into a practical training tool, providing step-by-step guidance for integrating investment analysis into CSA programming at national, district, and community levels. The manual is designed for Provincial and District Agricultural Officers; Extension Officers and Subject Matter Specialists; Policy and Planning Units of the Ministry of Agriculture; researchers; NGOs and development partners involved in CSA programming; and farmer organizations and cooperatives engaged in CSA adoption.